2016
DOI: 10.1120/jacmp.v17i3.5536
|View full text |Cite
|
Sign up to set email alerts
|

On the accuracy of dose prediction near metal fixation devices for spine SBRT

Abstract: The metallic fixations used in surgical procedures to support the spine mechanically usually consist of high‐density materials. Radiation therapy to palliate spinal cord compression can include prophylactic inclusion of potential tumor around the site of such fixation devices. Determination of the correct density and shape of the spine fixation device has a direct effect on the dose calculation of the radiation field. Even with the application of modern computed tomography (CT), under‐ or overestimation of dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…However, the underestimation of density due to the saturation of HU is larger for cobalt-chrome and the dosimetric uncertainty may be amplified. While the dosimetric effect of titanium hardware has been widely studied [8]- [14], to our best knowledge, this is the first study to evaluate the dosimetric effect of cobalt-chrome spinal hardware for single fraction and hypofractionated paraspinal IMRT and VMAT cases. Data is presented to support a clinical decision on the necessity to contour the hardware and assign the correct electron density for treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…However, the underestimation of density due to the saturation of HU is larger for cobalt-chrome and the dosimetric uncertainty may be amplified. While the dosimetric effect of titanium hardware has been widely studied [8]- [14], to our best knowledge, this is the first study to evaluate the dosimetric effect of cobalt-chrome spinal hardware for single fraction and hypofractionated paraspinal IMRT and VMAT cases. Data is presented to support a clinical decision on the necessity to contour the hardware and assign the correct electron density for treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published studies on the impact of spinal metal hardware on the dose calculation, and the beam delivery specific to spine SBRT using IMRT techniques [17] , [18] , [19] have been limited. For example, Son et al investigated the effects of titanium spinal implants on the dose calculated by the TPS for various delivery techniques such as ARTISTE, TomoTherapy and CyberKnife using three different types of imaging namely kVCT, extended kVCT and MVCT with an in-house homogeneous phantom with/without the titanium pedicle screws [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the plan that was compared was a simple plan as opposed to a highly complex spine SBRT plan. Cheng et al also evaluated the dose prediction accuracy near titanium hardware for spine SBRT using immersed gafchromic films embedded within an in-house water phantom with titanium spinal hardware [19] . A comparison between the measured and calculated doses for a simple plan with six open-fields was performed, and showed greater than 95% agreement with a gamma criterion of 2%/2mm for the commercial TPS dose calculation algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Supported by measurements in phantoms with a single beam or parallel-opposing beams, several studies have reported the dose perturbation by the spinal hardware. [3][4][5][6] Using Pinnacle dose calculation algorithm for a SBRT plan using step-shoot intensity-modulated radiation therapy (IMRT), Wang et al 7 found a ∼0.5 Gy dose decrease for seven cases with prescription dose of 24 Gy when manually overriding the physical density with the correct number. Using the Analytical Anisotropic Algorithm (AAA) algorithm from Eclipse planning system for one step-shoot IMRT and five volumetric modulated arc therapy (VMAT) plans, Tang et al 8 found the differences in V95% to the PTV between density override (DO) and no-DO calculations were within 1% for both titanium and cobalt-chrome implants, while the differences to maximum dose in the spinal cord were 0.02-0.18 Gy for titanium implants and 0.06-0.25 Gy for cobaltchrome implants.…”
Section: Introductionmentioning
confidence: 99%